Como-Harriet streetcar at Linden Hills Boulevard (Minnesota Streetcar Museum, 1953)
3fce62f2f4622b509bd334c9d4661cdc
A Como-Harriet streetcar approaches Linden Hills Boulevard on the west side of Lake Harriet. Streetcars of the Minnesota Streetcar Museum now operate here.
Minnesota
Hennepin
Linden Hills
Minneapolis
Harriet Lake
Mode of access: Internet.
Keywords: Twin Cities; streetcars; street scene; Transportation